Conceptual model for sustainable solid waste management in Abuja, Nigeria through assessment of related municipality operations in Abuja, Nigeria and Putrajaya, Malaysia - Ayuba, Kadafa Adati (2014)
Solid waste is one of the three major environmental problems in Nigeria, Malaysia and many other developing and even the developed countries are threatened by this. Waste management generally plays a significant role in the ability of nature to sustain life within its capacity and therefore an integral part of urban and environmental management in every city. Currently solid waste management is a globally challenging issue especially in developing countries, due to its adverse environmental effects. This research is a descriptive study using mixed method; survey and qualitative, aimed at using the integrated solid waste management system towards assessing the current state of solid waste management in Abuja and Putrajaya towards adopting a conceptual model for effective and sustainable waste management in Abuja. Residential and administrative questionnaire were used further supplemented with interviews and field observations toward obtaining a holistic assessment. The data obtained was analyzed using qualitative and quantitative methods; specifically descriptive, parametric and nonparametric statistics and theme analysis. The results obtain form the severity index analysis (Pj: Good 62.5 ≤ SI < 87.5 and Abj: Average 37.5 ≤ SI < 62.5) indicated Putrajaya has a better solid waste management system. With better waste management practices among the residents, a higher level (mean rank) of perception (Pj: 467.41 and Abj: 340.54), knowledge (Pj: 441.13 and Abj: 347.94) and satisfaction (Pj: 541.35 and Abj: 268.38) among residents. Although Abuja had a higher level of willingness (Abj:422.14 and Pj:382.95).The administrative parts of the assessment indicated more severe problems with solid waste management on the administrative level in Abuja but showed that problem did exist also in Putrajaya. In conclusion, Abuja showed a poor and unsustainable management of solid waste in the city, while the results of Putrajaya was indicative of a more definite waste management system but indicated the 3-R principal was not fully integrated in the current solid waste management system. A model was obtained toward improving the effectiveness and sustainability of solid waste management in Abuja based on issues that have been identified and determined from the assessment. In the correlation results for the conceptual model, finance/admin and others dimension would increase the effectiveness and efficiency of the waste management model by a 99% confidence level: r=0.623, p=0.003 with relation to services; r=0.602, p=0.005 with relation to equipment and r=0.711, p=0.001 with relation to others. Also others dimension would increase the effectiveness and efficiency of the waste management model by a 99% confidence level: r=0.618, p=0.004 with relation to services; r=0.675, p=0.001 with relation to equipment and r=0.711, p=0.001 with relation to finance/admin.